Grafted Chitosan-Hyaluronic Acid (CS-g-poly (MA-co-AN) HA) Complex Inhibits Fluconazole-Resistant Candida albicans Biofilm Formation - Chaitany Jayprakash Raorane; Divya Shastri; Asrafali Shakila Parveen; Rajesh Haldhar; Vinit Raj; Seong-Cheol Kim (MDPI AG, 2022)
Fungal resistance that leads to the failure of drug therapy due to biofilm development is a major clinical challenge. Various polysaccharides have been used to control biofilm formation by drug-resistant fungi, and this study was undertaken to develop chitosan (CS)-modified materials and evaluate their abilities to inhibit Candida biofilm growth. CS was grafted with methacrylamide (MA) and acrylonitrile (AN) and, to improve its application characteristics further, was grafted with hyaluronic acid to produce CS-g-poly (MA-co-AN) HA complex. Grafting and complex formation were confirmed using spectroscopic techniques. CS-g-poly (MA-co-AN) HA was tested to investigate its ability to inhibit Candida albicans biofilm formation and showed significant antibiofilm activity at 200 µg/mL. Additionally, CS-g-poly (MA-co-AN) HA did not have any toxic effect on Caenorhabditis elegans. Thus, this study provides an innovative means of preventing microorganism-associated biofilm formation.